Multiple Roles of Specialized Literacy Professionals: The ILA 2017 Standards. (23rd February 2018) - Bean, Rita M.; Kern, Diane
Abstract: This article compares the ILA 2017 Standards for preparing specialized literacy professionals with the 2010 Standards. The authors also describe levels of emphases for each specialized literacy role and implications of the new Standards for those serving in the field and for those who prepare them.